2022
DOI: 10.3390/agriculture12020273
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of Self-Incompatibility in Citrus by Temperature Stress, Bud Pollination and Polyploidization

Abstract: Self-incompatibility (SI) is present in around half of all species of flowering plants. SI limits endogamy and contributes to increased genetic diversity. SI is a very important trait in citrus because, when coupled with parthenocarpy, it allows seedless fruit production. Otherwise, SI is an impediment to genetic studies and breeding programs. Temperature stress, bud pollination and polyploidization can induce the breakdown of the SI mechanism in several species. In this work, we investigated how the SI mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…The inability of the dichogamous owers to develop fruits could be attributed to the high selfincompatibility reported for baobab by Venter et al (2017). Self-incompatibility is known in 50% of angiosperms (Montalt et al, 2022). The nding suggests that both self-compatibility and incompatibility are present in baobab trees, therefore self-pollination and cross-pollination are both possible.…”
Section: Resultsmentioning
confidence: 99%
“…The inability of the dichogamous owers to develop fruits could be attributed to the high selfincompatibility reported for baobab by Venter et al (2017). Self-incompatibility is known in 50% of angiosperms (Montalt et al, 2022). The nding suggests that both self-compatibility and incompatibility are present in baobab trees, therefore self-pollination and cross-pollination are both possible.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the incompatibility reaction appears to occur particularly late, just before anthesis. Moreover, tetraploidized self-incompatible citrus plants emerged to become self-compatible (Montalt et al, 2022;Yamashita et al, 1990). More on this subject is mentioned in a later section.…”
Section: General Features Of Citrus Self-incompatibilitymentioning
confidence: 99%
“…Some practical methods to break SI have been reported. Bud pollination (Distefano et al, 2009b;Montalt et al, 2022;Wakana et al, 2004), repeated pollination of immature buds (Yamashita, 1980(Yamashita, , 1981, and hightemperature treatment (Aloisi et al, 2020) can artificially break the SI in Citrus species. Wakana et al (2004) reported that the most appropriate time for producing self-fertilized seeds by the bud pollination of selfincompatible Citrus species is when flowers are half of their total length.…”
Section: General Features Of Citrus Self-incompatibilitymentioning
confidence: 99%
See 2 more Smart Citations